2016
DOI: 10.1038/ncomms10300
|View full text |Cite
|
Sign up to set email alerts
|

Social and novel contexts modify hippocampal CA2 representations of space

Abstract: The hippocampus supports a cognitive map of space and is critical for encoding declarative memory (who, what, when and where). Recent studies have implicated hippocampal subfield CA2 in social and contextual memory but how it does so remains unknown. Here we find that in adult male rats, presentation of a social stimulus (novel or familiar rat) or a novel object induces global remapping of place fields in CA2 with no effect on neuronal firing rate or immediate early gene expression. This remapping did not occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
186
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 163 publications
(207 citation statements)
references
References 62 publications
19
186
2
Order By: Relevance
“…77)—recent data seem to indicate that CA2 may be especially important for temporal 78 and social 7981 memory. There is not nearly enough data on CA2, and it will be important to know the extent to which the representational scheme in CA2 parallels the more well-known subfields.…”
Section: Do Hippocampal Pyramidal Cells Reliably Encode Nonspatial Inmentioning
confidence: 99%
“…77)—recent data seem to indicate that CA2 may be especially important for temporal 78 and social 7981 memory. There is not nearly enough data on CA2, and it will be important to know the extent to which the representational scheme in CA2 parallels the more well-known subfields.…”
Section: Do Hippocampal Pyramidal Cells Reliably Encode Nonspatial Inmentioning
confidence: 99%
“…85). CA2 neurons also had a higher mean firing rate than CA1 and CA3 neurons 30,85 . Together, these findings indicate that CA2 neurons carry less spatial information than those in the other CA regions.…”
Section: Role In Behaviourmentioning
confidence: 90%
“…One study examined how social stimuli such as exposure to either novel or familiar animals would influence CA2 neuron firing in rats 30 . The authors of this study found that place fields shift significantly in response to social stimulation (that is, global remapping; see FIG.…”
Section: Role In Behaviourmentioning
confidence: 99%
See 2 more Smart Citations